Ethical and sustainable supply chain management in a global context - Akkucuk, Ulas, 1975- (Business Science Reference, an imprint of IGI Global, 2019)
"This book examines ethics and sustainability as it relates to managing a global supply chain. It also provides insights and support to executives concerned with the management of a sustainable enterprise"--